Leveraging mouse genetic diversity to investigate the role of brain myeloid cells in Alzheimer's disease: Inflammation: From basic science to biomarkers. (7th December 2020) - Yang, Hongtian Stanley; Onos, Kristen; Choi, Kwangbom; Keezer, Kelly; Diemler, Cory; Hewes, Amanda; O'Rourke, Rita; O'Rourke, Sarah; Gastoukian, Nils; Harder, Jeffrey; Skelly, Daniel; Sasner, Michael; et al.
Abstract: Background: Myeloid cells have been strongly implicated in Alzheimer's Disease and related dementias (ADRDs). Our previous study showed genetic diversity significantly modified brain myeloid cell responses and AD‐relevant phenotypes in mice. Therefore, incorporating natural genetic variation into mouse models is indispensable to understand the role of myeloid cells in AD. This study aims to characterize brain myeloid cells in our genetically diverse AD panel to determine their functions in ADRDs. Methods: Brain myeloid cells were isolated from 8‐9 months‐old female mice from our genetically diverse AD mouse panel [C57BL/6J (B6), PWK/PhJ, WSB/EiJ and CAST/EiJ strains, each carrying APP/PS1 ] using magnetic activated cell sorting and were subjected to single‐cell RNA‐sequencing (scRNA‐seq). Data were processed using a customized pipeline allowing strain‐specific genome alignment followed by downstream analyses using Seurat and edgeR packages. Differences in myeloid cell responses between strains are being validated using functional assays in primary microglial cultures and immunofluorescence. To identify the putative genetic variations that drive and/or modify differences in myeloid cell responses, quantitative trait locus mapping of microglia number and morphology is being performed in brains from 120 Diversity Outbred (DO) mice, derived from eight mouse strains including those listed above. Results: scRNA‐seq uncovered heterogeneous clusters of myeloid cells that vary significantly in cell abundance and gene expression between both wild‐type and APP/PS1 of B6, PWK, WSB and CAST mice. There was a significantly lower percentage of disease‐associated microglia in WSB. APP/PS1 mice and a significantly higher percentage of interferon‐responding microglia in PWK .APP/PS1 mice, compared to other AD strains. These data agreed with previously determined phenotype differences between strains. Differential gene expression analyses (all data compared to the B6 strain) revealed robust APP/PS1 ‐responding genes unique to strain background (strain by genotype effect) including Rpl29, Irf7, Cd36, H2‐Eb1, Lag3 and Cd34 in CAST; Ramp, Tmem176a, Tmem176b, Sepp1 and Inpp5d in PWK, and Ccl6, Slamf8, Nme1 and Pcna in WSB strain. Validation by primary culture and analyses of DO mice are underway. Conclusion: As in humans, mouse genetic diversity significantly impacts the landscape and dynamics of brain myeloid cells in AD. These studies will improve the translatability of myeloid‐based therapies for ADRDs.